Virtual design of multi-axis positioning for robotics application - Wan Muhd Zulhasifi, W. Ab. Rahim (2008)
With the development of information technology, virtual design is now considered as one of the most important phases in the process of the overall design in engineering. In this project, multi-axis positioning was virtually design using general-purpose finite element code with the intention of application in robot structure. Robot model Fanuc M-6iB was chosen for reference and virtual robot having five axis similar to the reference robot was designed. The 3D geometry of multi-axis integrated into the robot was created in Solidworks. Solidworks model was then imported into finite element (FE) environment for physical analysis. By using pin joint method and manipulating boundary conditions available in the FE package, motion of each manipulator was defme. The element types used for manipulators and joints were 8-node brick and beam element respectively. Materials were specified according to the published report. Currently, linear material model was assumed. Mechanical event simulation was employed to analyze dynamic behavior of the manipulators. Physical response such as stress, strain due to dynamic effect were predicted. Finite element predictions provide consistent rotational displacements with the reference robot. Stress, strain and deformation were also find to be reasonable.